The experience of novelty: another dimension to subjective memory experience? - Staley, Shelly, author; Cleary, Anne, advisor; Seger, Carol, committee member; Hoke, Kim, committee member (Colorado State University. Libraries, 2014)
Subjective experiences of memory (e.g., feelings of familiarity) have been a topic of much research. Though novelty might be considered a manifestation of memory (insofar as some form of memory for the past is required in order for novelty recognition or detection to occur), subjective experiences of novelty have largely been ignored in the current memory literature. The present study used a rating scale to measure the subjective feeling of novelty. One goal was to investigate potential mechanisms of feelings of novelty. Another was to determine how feelings of novelty relate to feelings of familiarity; for example, many models assume that novelty is simply the inverse of familiarity. Two experiments reported here examined if this presumed relationship between familiarity and novelty is an accurate assumption. In one experiment, subjects viewed words in a study list and then were tested on cues that potentially shared orthographic features with the study words while duration of cue-prime exposure and cue-match-priming effects were observed. In another, subjects were tested after having repeated the test cues aloud either once or 30 times. Both experiments compared a familiarity rating scale with a novelty rating scale. No effects of duration of exposure (either through priming in Experiments 1 and 2 or repetitions in Experiment 3) were observed, helping to rule out several potential mechanisms of feelings of novelty. Differences in how familiarity ratings and novelty ratings responded to the experimental manipulations were found in both experiments, suggesting that the sense of novelty is not simply the inverse of familiarity.
Keywords: familiarity; recognition; novelty; fluency